The Effect of Compensation on The Performance of PT Employees. Seacon Bintang Sejahtera Jakarta - Harianto, Pendi; Irawan, Pristanto Ria; Darka, Darka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to analyze the effect of compensation on the performance of employees of PT. Seacon Bintang Sejahtera Jakarta. Compensation is an important factor in human resource management that can influence employee motivation, performance and productivity. This research uses a quantitative approach with a saturated sampling method on 44 employees from various levels at PT. Seacon Bintang Sejahtera Jakarta. Data was collected through a structured questionnaire that measures employee perceptions of the company's compensation system and performance appraisal. Data analysis was carried out using a simple linear regression method to test the research hypothesis. The results of this research show that there is a compensation effect regularly partial impact on the performance of employees of PT. Seacon Bintang Sejahtera Jakarta. These findings imply the importance for companies to design and implement a comprehensive and fair compensation system to improve employee performance. This research also recommends the need for regular evaluation of the compensation system to ensure its effectiveness in encouraging optimal employee performance.